IMPLEMENTASI METODE TEAMS GAMES TOURNAMENT (TGT) TERHADAP PEMBELAJARAN INFORMATIKA SMP MATERI BERFIKIR KOMPUTASIONAL - Kirom, M; Handayani, Anik Nur; Srini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of implementing the Teams Games Tournament (TGT) method in Informatics learning at the junior high school level, particularly in the topic of computational thinking. A mixed-methods approach was employed, combining quantitative and qualitative methods through a quasi-experimental design involving two student groups: an experimental group using the TGT method and a control group employing conventional teaching methods. The findings indicate that the implementation of TGT significantly improves students’ learning outcomes and creative thinking skills. Data analysis revealed that students in the experimental group achieved higher average scores compared to those in the control group, suggesting that the TGT method is effective in enhancing student motivation and participation in the learning process.